All‐Polymer Bulk Heterojuction Solar Cells with 4.8% Efficiency Achieved by Solution Processing from a Co‐Solvent. (15th July 2014) - Earmme, Taeshik; Hwang, Ye‐Jin; Subramaniyan, Selvam; Jenekhe, Samson A.
<x xml:space="preserve">Abstract</x> All‐polymer solar cells with 4.8% power conversion efficiency are achieved via solution processing from a co‐solvent. The observed short‐circuit current density of 10.5 mA cm−2 and external quantum efficiency of 61.3% are also the best reported in all‐polymer solar cells so far. The results demonstrate that processing the active layer from a co‐solvent is an important strategy in achieving highly efficient all‐polymer solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>